Twenty-five centuries of technological change : an historical survey - Mokyr, Joel, 1946- (Fundamentals of pure and applied economics, 1990)
Mokyr provides a long term perspective on the economic impact of technological change, surveying developments in production technologies between 500 BC and 1914.